Effect of different post-partum therapeutic protocols with intrauterine oxytetracycline, oxytocin and/or GnRH injection in post-kidding goats on oxytetracyclines residues in goat milk and postpartum ovarian resumption with referring to clinical and haematological pictures - Asem M. Zakaria; Taher Al-Daek; Enas Elmeligy; Ragab H. Mohamed; Eman M. Abu El-Naga; Haitham H. Mohammed; Abdulrahman Abdulkarim; Mohammed Abdelhadi Ali; Khaled. A. Khesruf; Arafat Khalphallah (BMC Veterinary Research, 2023)
Abstract Background The post-parturient period in goat had marked changes in an animal’s endocrine and metabolic status as well as by reduction in feed intake when the nutrient demand for impending lactogenesis was increasing. The current study aimed to monitor the residues of oxytetracycline in Baladi goat milk and their hazards on public health as well as the time required until complete disappearance of this medicament from milk through following up periods included 0, 12, 24, 36, 48, 60, 72, 84, 96 and 120 h in post-kidding goat following intrauterine application of oxytetracycline. The study also compared between the efficacy of oxytetracycline only, oxytetracycline with oxytocin, or oxytetracycline with GnRH, through monitoring the clinical findings and haematological pictures at days 0, 5 and 7 post-partum as well as studying the changes in numbers and size of follicles at days 15, 30 and 45 postpartum after different treatments strategies in different groups i.e. Control healthy goat (Contgr), Oxytetracycline treated goat (Oxytetgr), Oxytetracycline-oxytocin treated goat (Oxytet-Oxytogr) and Oxytetracycline-GnRH treated goat (Oxytet-GnRHgr). The study was carried out on clinically healthy Baladi goats (n = 40) that gave birth recently. They were divided into 4 equal groups (n = 10 goats for each); Contgr which received no medication after birth, Oxytetgr which administrated oxytetracycline tablets intrauterine at day of birth, Oxytet-Oxytogr which treated by oxytetracycline tablets intrauterine at day of birth followed by oxytocin injection at 3rd day after birth, and Oxytet-GnRHgr which treated by oxytetracycline tablets intrauterine at day of birth followed by GNRH injection at 3rd day after birth. Results and Conclusions The study concluded the highest oxytetracyclines residues in goats’ milk were reported after 36 h following intrauterine oxytetracycline application where complete disappearance of oxytetracyclines residues in goats’ milk required 120 h elapsed after intrauterine oxytetracycline application in which the goats milk became safe for human consumption. The study also reported powerful influence of the applied variable therapeutic regimens on post-partum ovarian resumption through clear significant variations in numbers and sizes of follicles either between different goats’ groups within the same day, or between days 15, 30 and 45 post-partum within each independent goat group.